The history and welfare of working mules in the valleys of the Toubkal massif, in the High Atlas of Morocco - Cousquer, Glen; Alyakine, Hassan; Lindsay-McGee, Victoria (Frontiers in Veterinary Science, 2023)
The appearance of the mule in the remote villages of the Toubkal National Park in the High Atlas mountains of Morocco can be traced back to the early years of the twentieth century.The mule population's subsequent growth in numbers accompanied the shift away from a subsistence economy that was made possible by the appearance and growth of the mining and mountain tourism industries. This paper reviews this early history, drawing on the accounts provided by early explorers and anthropologists, before developing a mixed methods approach to evaluating the welfare of pack mules in two villages within the National Park. The first village is part of the main access route to the Toubkal, the principle summit of the National Park and therefore much visited. The second is a much more remote, under visited and less developed village. Ethnographic work, studying muleteering practice and undertaken over several years is reported here and supplemented by findings from a detailed survey of the mules of both villages. This allows the work undertaken and the lived realities of the working mule across several generations of inhabitants to be presented together with data about the primary welfare concerns identified on clinical examination. In village one, 72 mule owners and their mules were surveyed and examined.Many of these mules worked in tourism, providing a source of revenue for their families.This work was often undertaken by teenagers / young adults working their father's mules.Tethering was widely practised and evidence of tethering injuries were identified in most mules. In the more remote village, 18 owners and their equids were surveyed and examined. In this population, mules were more likely to be worked locally in agriculture, building and to collect firewood. Bitting injuries associated with the use of the traditional bit were a significant concern in both villages. The universal use of a closed shoe was also in evidence in both villages; this was associated with atrophy of the frog and hoof imbalances.The reasoning for the use of the traditional bit and closed shoe are presented and alternatives discussed.